Microplastics in different environmental compartments in India: Analytical methods, distribution, associated contaminants and research needs - S. Veerasingam (9648980) (2020)
This study aims at reviewing the scientific literature related to microplastic (MP) pollution in various environmental matrices in India and highlighting the research gaps for future research priorities. Currently used methods for sampling, extraction, identification, characterization and quantification of MPs were assessed, and sources, distribution, transport pathways, fate, impacts, chemical risks and MP-biota interactions in the marine and freshwater ecosystems of India were examined. Studies on the spatial and temporal transport pathways of MPs are very scarce, especially w.r.t. river discharge, anthropogenic activities, beach morphology, bottom topography, biofouling and hydrodynamics. Though some amount of baseline data of MPs at select regions along the Indian coast have been generated, the extent of MP pollution in air, major rivers and nearshore continental shelf is still poorly understood. Moreover, this study highlights an urgent need for the harmonized and standardized sampling and analytical methods for MP research, that can enable us to study the spatial and temporal comparisons around the world meaningful. Other Information Published in: TrAC Trends in Analytical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.trac.2020.116071